Accounting Students' Perception of The Importance of Ethics in Audit Practice - Kenswary, Dhea; Rapina, Rapina (Maksi, 2025)
Audit practice requires high professional standards to ensure financial transparency and accuracy. Professional ethics play an important role in maintaining the quality and credibility of the audit process. This study examines accounting students' perceptions of ethics in audit practice, which has rarely been explored in previous research. The quantitative method was used with Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique through SmartPLS. Data was collected from 139 students who had taken the audit course. The findings reveal that integrity, confidentiality, and professional behavior significantly influence audit practice, but objectivity and professional competence do not show a statistically significant influence audit practices. This study highlights the importance of ethics education in shaping competent and ethical auditors. The results provide insights for improving ethics curricula in accounting education and supporting future audit practice regulations.